Revolutionizing tumor diagnosis and treatment: the promise of DNA nanotechnology - Zhou, Yi; Wang, Ning (Frontiers in Immunology, 2025)
Tumors represent a significant challenge to human health, with ongoing difficulties in their diagnosis and treatment. Over recent decades, DNA nanotechnology has emerged as a promising field, demonstrating substantial advancements in drug delivery and disease diagnosis. The inherent biocompatibility and programmability of DNA nanostructures allow for their tailored design and assembly, facilitating the delivery of various therapeutic agents. Due to their ease of modification, these nanostructures can be functionalized to recognize specific targets, enabling the targeted drug delivery and minimizing the adverse effects. Furthermore, DNA nanotechnology contributes to the rapid and sensitive detection of tumor biomarkers, enhancing the early-stage diagnosis of malignant tumors. This article comprehensively reviews advancements in DNA nanomaterial applications for tumor diagnosis and treatment. First of all, in the aspect of tumor diagnosis, this review focuses on the research of DNA nanostructures in the detection of tumor biomarkers, and then introduces the application of DNA nanostructures in tumor therapy, including chemotherapy, gene therapy and immunotherapy. Finally, we summarized the challenges and opportunities of DNA nanomaterials in biomedical research and clinical applications. This review systematically organizes key innovations: (1) first comprehensive analysis of DNA nanostructures design principles for the applications in tumor diagnosis and therapy, and (2) original proposal for overcoming clinical translation barriers through precise design and assembly of DNA nanostructures.